Proteomic Profiling Reveals Upregulated Protein Expression of Hsp70 in Keloids. (24th October 2013) - Lee, Ju Hee; Shin, Jung U.; Jung, Inhee; Lee, Hemin; Rah, Dong Kyun; Jung, Jin Young; Lee, Won Jai
Abstract : Background. The biochemical characteristics of keloid-derived fibroblasts differ from those of adjacent normal fibroblasts, and these differences are thought to be the cause of abnormal fibrosis. Therefore, we investigated the characteristic proteins that are differentially expressed in keloid-derived fibroblasts using proteomics tools. Objective. We attempted to investigate the novel proteins that play important roles in the pathophysiology of keloids. Methods. Proteomics analysis was performed to identify differentially expressed proteins in keloid-derived fibroblasts. Keloid-derived fibroblasts and adjacent normal fibroblasts were analyzed with 2-DAGE. We validated these proteins with immunoblot analysis, real-time RT-PCR, and immunohistochemistry. Results. Sixteen differentially expressed protein spots were identified in keloid-derived fibroblasts. Among them, heat shock protein 70 (Hsp70) was specifically upregulated in keloid-derived fibroblasts. Also, immunohistochemistry and western blot analysis revealed increased Hsp70, TGF- β, and PCNA expressions in keloids compared to normal tissue. Conclusion. Hsp70 is overexpressed in keloid fibroblasts and tissue. The overexpression of Hsp70 may be involved in the pathogenesis of keloids, and the inhibition of Hsp70 could be a new therapeutic tool for the treatment of keloids.